Radiation-Induced Fibrosarcoma in the Stoma: A Case Report and Literature Review - Zhao Li; Liang Fang; Liang Lv; Xinjia He; Wenqiang Luo; Dong Guo; Zhen Liu (Case Reports in Surgery)
Fibrosarcoma is a rare malignant neoplasm consisting of fibroblasts with a large variety of collagen production. They usually involve deep soft tissues in extremities and trunk. However, fibrosarcoma can be seen in fields that received previous irradiation. Here, we report a case of parastomal fibrosarcoma after laparoscope-assisted extra-levator abdominal perineal resection (ELAPE) and colostomy. Prior to surgery, the patient underwent neoadjuvant chemoradiotherapy. The patient received extensive stomal lumpectomy and stoma reconstruction. The patient is free of local or distal recurrence for 1 year and died 4 years after diagnosis.